Institutions and Growth in the Arab and Middle Eastern Countries - Harb, Georges (International Journal of Economics and Financial Issues, 2017)
We assess the impact of the quality of public institutions on economic growth during the period 1995-2013 in the Arab and Middle Eastern (AME) countries. We use a sample of 99 countries, of which 17 AME countries, and employ a dynamic panel approach that controls for unobserved heterogeneity, common shocks affecting the sample countries, and accounts for the endogeneity of the regressors. From a global standpoint, the impact of institutions on growth seems to be depending on the development level. From a regional perspective, the effect of institutions on economic outcome in the AME countries is found positive but insignificant. The prevalence of extractive industries could explain the insignificant effect of institutions on economic performance in some AME countries. In others, the insignificant result is likely to reflect shortages in technological readiness and inefficient resource-allocation policies. Keywords: Arab and Middle Eastern countries; growth; institutions; corruption; dynamic panel estimation JEL Classifications: O43, O47